Phase diagrams of Ar-Xe, Kr-Xe, and Kr-CO binary alloys - Yantsevich, L.D.; Prokhvatilov, A.I.; Barylnik, A.S. (Физика низких температур, 1996)
Using the powder x-ray diffraction method, the phase diagrams of the binary systems Ar-Хе, Kr-Xe, and Kr-CO have been studied. The molar volumes of these solutions versus temperature and composition have been determined within the homogeneity regions. A considerable deviation of the solubility from the Hume-Rosery rules (which is valid for metal alloys) has been found.